Formulation of Herbal Toothpaste Combination of Anna Apple Peel and Kaffir Lime Peel with Variation of Sodium Lauryl Sulfate Concentration - Nila Sastrawati, Andi; Jumain, Jumain; Arisanty, Arisanty (Riviera Publishing, 2023)
Toothpaste is a preparation whose use aims to clean the mucous membranes of the mouth. Anna's apple is a fruit that contains malic acid which has the ability to whiten teeth. Kaffir lime contains essential oils that have effects as antibacterial, antifungal and refreshing. This study aims to formulate herbal toothpaste preparations a combination of Anna Apple Skin extract (Malus domestica) and Purut Orange Peel extract (Citrus hystrix) and determine the physical quality of the preparation made. This type of research is experimental research using maceration methods with physical quality stability testing, namely organoleptic observations, homogeneity, pH, foam height, viscosity, and dispersion. In this study, two herbal toothpaste formulations were made with variations in the concentration of Sodium Lauryl Sulfate as a foaming agent in toothpaste. From the results of the study, it was obtained that the combination of the two extracts can be formulated into herbal toothpaste preparations and based on the results of physical quality tests, both formulations with variations in the concentration of Sodium Lauryl Sulfate 1.5% and 2.5% meet the requirements of the established standards.